Stretching the truth: The effects of static and dynamic stretching protocols on strength and power performance. - Gill, A. H. (Journal of Australian Strength and Conditioning, 2016)
The intent of this review of literature was to highlight the physiological responses of two common forms of pre-exercise stretching, being static and dynamic, and more importantly determine whether one form achieves improved performance for the individual. Accumulation of literature using an online search database known as Summon, plus specific databases such as Journal of Strength and Conditioning Research, incorporated 31 relevant articles in the review. Findings dictate warm ups involving acute bouts of static stretching prior to exercise which is strength or power dominant produced results ranging from no change in performance outcome to significantly reducing capabilities of the individual in movements such as jumping, sprinting or maximal voluntary contractions. In comparison, implementing dynamic stretching during warm up displayed increases in performance outcomes related to strength and power. Physiological responses hypothesised to be responsible for producing negative performance following static stretching are related to reduced musculotendinous unit stiffness, which increases compliance of the muscle complex; and neural mechanisms such as reduced muscle activation. Conversely, for dynamic stretching proposed physiological responses indicating a positive performance improvement were increased muscle temperature and activation of the post-activation potentiation mechanism. In conclusion, this article highlights the potential for discarding warm up protocols which involve static stretching and including dynamic stretching if the intended performance outcome is highly dependent upon maximal strength or power production, based on physiological responses which occur in relation to either form of stretching.